Success of Women Entrepreneurs: An Empirical Study on Indian Women Entrepreneurs - PAL, BRAJABALLAV; MISHRA, SURABHI (International Journal of Psychosocial Rehabilitation, 2024)
This study endeavored to primarily investigate the success factors of small and medium scale women run businesses in Kolkata, India. Other crucial objectives of the investigation included finding about the challenges faced by these female entrepreneurs, difference in perception of success factors by educated and uneducated women entrepreneurs, and the factors that compel (push) & motivate (pull) these women to start their own business. The study is exclusively based on primary data collected through a self-administered questionnaire filled by over 130 women entrepreneurs. Descriptive statistical tools such as percentage, frequency, rank order, weighted average and standard deviation were used to analyze the data. T-test analysis was conducted to analyze the difference between the perception of success factors for educated and uneducated women entrepreneurs. The results reveal that women consider personal attributes like skills, business ethics and good customer relation as the most crucial success factor to a business. Challenges faced are mostly gender based leading to low self-esteem. Unemployment pushes women into entrepreneurship whereas desire for economic independence pulls or motivates them to enter entrepreneurship.